Stock ownership guidelines for CEOs: Do they (not) meet expectations? - Benson, Bradley W.; Lian, Qin; Wang, Qiming (Journal of Banking & Finance, 2016)
This paper examines the determinants and the effects of CEO stock ownership guideline adoption, differentiating Not-meet/Meet adopters – those setting the guideline above/below the CEO’s stock ownership at the time of adoption. While Meet adoption is mainly determined by factors related to stakeholder management, we find that Not-meet adoption is associated with factors related to both incentive alignment and stakeholder management. CEO ownership increases and CEO incentive alignment improves for Not-meet firms. But CEO ownership and incentives are unchanged for Meet firms following guideline adoption. We find no evidence that CEO compensation changes abnormally after adoption. Not-meet firms have larger improvement in operating performance and better stock performance than Meet firms. We provide evidence that the motives and the effects of guideline adoption depend on the level of the ownership restriction relative to the CEO’s ownership at the time of adoption.